2015
DOI: 10.1021/acs.jpcc.5b08783
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-fold Enhancement of Gadolinium-Porphyrin Phosphorescence at Room Temperature by Free Gadolinium Ion in Liquid Phase

Abstract: The influence of free gadolinium ion (Gd3+) on room-temperature phosphorescence (RTP) of gadolinium labeled hematoporphyrin monomethyl ether (Gd-HMME) was studied. Twenty-fold enhancement of Gd-HMME RTP by the titration of free Gd3+ was achieved. We found that the absorption from the ground (S 0) to singlet excited states of Gd-HMME did not change with the addition of Gd3+, which means that the phosphorescence quantum yield has been tuned from 1.4% to 28%. According to the excitation spectra, the transition po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…It is well-known that porphyrins possess very strong excited state absorption from both the triplet as well as the singlet states, singlet excited state has a shorter lifetime and transfers the excited state energy to triplet state through inter system crossing (ISC) . Porphyrin molecules typically emit in the 600–700 nm range due to radiative relaxation. , However, after attachment of POM on porphyrin molecules, energy difference of singlet and triplet excited states of hybrids 1 and 2 are very small which speed up the ISC process, ,, consequently enhance the optical nonlinearities of the resulting hybrids , while the luminescence is quenched by rapid photo induced electron transfer from triplet excited state porphyrin molecules to Dawson POMs (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that porphyrins possess very strong excited state absorption from both the triplet as well as the singlet states, singlet excited state has a shorter lifetime and transfers the excited state energy to triplet state through inter system crossing (ISC) . Porphyrin molecules typically emit in the 600–700 nm range due to radiative relaxation. , However, after attachment of POM on porphyrin molecules, energy difference of singlet and triplet excited states of hybrids 1 and 2 are very small which speed up the ISC process, ,, consequently enhance the optical nonlinearities of the resulting hybrids , while the luminescence is quenched by rapid photo induced electron transfer from triplet excited state porphyrin molecules to Dawson POMs (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…41 Porphyrin molecules typically emit in the 600−700 nm range due to radiative relaxation. 84,85 However, after attachment of POM on porphyrin molecules, energy difference of singlet and triplet excited states of hybrids 1 and 2 are very small which speed up the ISC process, 41,86,87 consequently enhance the optical nonlinearities of the resulting hybrids 86,88 while the luminescence is quenched by rapid photo induced electron transfer from triplet excited state porphyrin molecules to Dawson POMs (Figure 9).…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…The room temperature phosphorescence in porphyrins is always absent as the forbidden transition from the excited triplet state (T 1 ) to the ground state (S 0 ). The decoration of porphyrin rings by heavy metal ions can break this forbidden process, which is known as the heavy atom effect (HAE). Conventionally, the intensity and lifetime of phosphorescence had been employed to evaluate the functionality of the HAE. For instance, Shi et al reported that the phosphorescence quantum yield (Φ P ) of PDBCz is 15 times higher than its parent compound PDCz once the bonds of halogen Br ions and porphyrin rings are introduced .…”
Section: Introductionmentioning
confidence: 99%
“…The most well known and efficient phosphorescent compounds are in the organometallic family of chromophores, such as metal suldes or metal-cored porphyrins. 15,20,[25][26][27][28][29][30] However, fabrication of these kinds of molecules is neither cheap nor environmentally sound. The design of bio-friendly organic compounds for phosphorescent applications which are not limited by temperature or open-air is extremely difficult as the coupling between singlet and triplet excited states is typically quite weak.…”
Section: Introductionmentioning
confidence: 99%